Prevalence and determinants of hypertension among men and women in Maharashtra: an analysis of NFHS-5 data 2019-2021 - Suryawanshi, Jidnyasa; Narayan, Raj; Yadav, D. K. (International Journal Of Community Medicine And Public Health, 2026)
Background: Hypertension is a major underlying factor in India’s rising non-communicable disease burden and poses a significant public health challenge. This study investigated the prevalence and identifies key determinants among men and women in Maharashtra. Methods: This cross-sectional study used data from the National Family Health Survey (NFHS-5, 2019-2021). Statistical analysis was conducted using SPSS for descriptive statistics and logistic regression, we explored associations between hypertension and comprehensive set of factors including demographic attributes (age, gender, marital status, education), socioeconomic status (wealth index quintiles, religion, caste/tribe), geographic (urban/rural residence, region), health (diabetes status), and lifestyle (tobacco use, alcohol consumption). Results: Our results showed that hypertension occurs significantly more often with age and is generally higher in women. Wealthier individuals in urban settings exhibit a higher prevalence, with some regional differences across the state. A strong correlation was found between diabetes and hypertension, and lifestyle habits such as tobacco and alcohol use were significantly associated with elevated blood pressure. Conclusions: Hypertension in Maharashtra is influenced by complex mix of factors, such as age, socioeconomic status, geography, and modifiable risk behaviours, to a significant extent. High prevalence, especially in women and wealthier populations, coupled with the diabetes link and far-reaching lifestyle impacts, underscores an urgent public health priority. These findings highlight focused public health initiatives and awareness programs, lifestyle intervention, and better healthcare access in Maharashtra to manage and prevent hypertension, a growing non-communicable disease burden.